Correlation between proton conductivity, thermal stability and structural symmetries in novel HPW-meso-silica nanocomposite membranes and their performance in direct methanol fuel cells - Zeng, J.; Shen, P.; Lu, S.; Xiang, Y.; Li, L.; De Marco, Roland; Jiang, San Ping (Elsevier B.V, 2012)
The intrinsic relationship between proton conductivity, thermal stability and structural symmetries of phosphotungstic acid (HPW)-functionalized mesoporous silica (HPW-meso-silica) membrane was investigated with mesoporous silica from 2D hexagonal p6mm, 3D face-centered cubic (Fm¯3m), body-centered Im¯3m, to cubic bicontinuous Ia¯3d symmetries. HPW-meso-silica nanocomposites with 3D mesostructures display a significantly higher proton conductivity and higher stability as a function of relative humidity in comparison to 2D mesostructures. The best result was obtained with body-centered cubic (Im¯3m)-HPWmeso-silica, showing proton conductivities of 0.061 S cm-1 at 25°C and 0.14 S cm-1 at 150°C, respectively, and an activation energy of 10.0 kJ mol-1. At 150°C, the cell employing a HPW-meso-silica membrane produced a maximum power output of 237 mW cm-2 in a methanol fuel without external humidification. The high proton conductivity and excellent performance of the new methanol fuel cells demonstrate the promise of HPW-meso-silica nanocomposites with 3D mesostructures as a new class of inorganic proton exchange membranes for use in direct methanol fuel cells (DMFCs).